A comparison of self-report measures of callous-unemotional traits among incarcerated youth: associations with aggression, conduct disorder, and offending behavior - Ray, James V. (Criminal justice and behavior, 2016)
The current study compared the psychometric properties and incremental validity of the callous-unemotional (CU) traits dimensions from four self-report measures of youth psychopathic traits, including the Antisocial Process Screening Device Self-Report version (APSD-SR), the Youth Psychopathic Traits Inventory (YPI), Youth Psychopathic Traits Inventory?Short version (YPI-S), and the Inventory of Callous-Unemotional Traits (ICU) among a sample of male youth incarcerated in Portuguese detention centers (N = 221). Across these measures, estimates of reliability and internal consistency were generally good; however, the correlations between measures ranged from very low to high suggesting moderate convergent validity. With regard to incremental validity, the Callousness dimension of the ICU was the best predictor of aggression, conduct disorder, and crime seriousness, whereas the Uncaring dimension of the ICU was the best predictor of age of crime onset. The current findings have important implications regarding the assessment of CU traits.